2013
DOI: 10.1039/c2ra22297c
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study on the doping effects of nitrogen on the electronic structure and optical properties of Cu2O

Abstract: Recent experimental literature (Sol. Energ. Mat. Sol. Cells, 2012, 105, 192) has reported that nitrogen doped Cu 2 O is a possible material for novel intermediate band solar cells. The doping effects of nitrogen on the crystal structure, electronic structure, and optical properties of Cu 2 O have been studied by an ultrasoft pseudopotential plane wave method based on first-principles calculations. The results show that nitrogen doping slightly widens the band gap of Cu 2 O, and form an intermediate band in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 33 publications
1
28
1
Order By: Relevance
“…However, all U out values are still larger than 14 eV, while all empirically fitted U eff values range from 6 to 8 eV. 10,[15][16][17][18][19] Moreover, the increasing U in parameter should open the band gap and diminish the nonlinear behavior of the density functional, thus leading to smaller U out . This expected decreasing trend is found, e.g., in ferromagnetic (open-shell) bcc Fe calculations 5 but does not occur in the present Cu 2 O case.…”
Section: Resultsmentioning
confidence: 99%
“…However, all U out values are still larger than 14 eV, while all empirically fitted U eff values range from 6 to 8 eV. 10,[15][16][17][18][19] Moreover, the increasing U in parameter should open the band gap and diminish the nonlinear behavior of the density functional, thus leading to smaller U out . This expected decreasing trend is found, e.g., in ferromagnetic (open-shell) bcc Fe calculations 5 but does not occur in the present Cu 2 O case.…”
Section: Resultsmentioning
confidence: 99%
“…189 Based on the widening of the band gap of N-doped Cu 2 O, it is very likely that it would absorb at a maximum rate across the solar light spectrum, from the near infrared region to the ultraviolet region, and hence can be considered as a perfect intermediate band (IB) material, which can improvise the solar cell performance. 189 Recently, Mittiga et al 190 first reported that nitrogen doped Cu 2 O could act as a possible material for 3rd generation IB solar cells. …”
Section: A Review On Cu 2 O and Cu I -Based P-type Semiconducting Tramentioning
confidence: 99%
“…Cu 2 O, with an intrinsic direct band gap of 2.17 eV 11 , making it one of the most promising photocatalysts for environmental clean up, photogeneration of hydrogen from water, and solar energy utilization, has been tested as a visible-light driven photocatalyst directly for splitting water and degradation of organic pollutants 12,13 . Further advantages are nontoxicity, low-cost production processing and the fact that its component elements are very abundant 14 . Moreover, the band alignments of Cu 2 O satisfy the requirement as mentioned above with a CBM (-1.4 eV) far above the hydrogen production level (-0.65 eV) and VBM (+0.77 eV) slightly below the water oxidation level (+0.57 eV) at pH=7 (see Figure 1 Unfortunately, the practical application of Cu 2 O in solar hydrogen production is still severely hindered by its low photocatalytic efficiency due to two major reasons: Firstly, the even-parity symmetry of the CBM and VBM states in Cu 2 O prohibits the band-edge radiative transition, which has hindered its potential use in optical applications 11,16,17 .…”
Section: Introductionmentioning
confidence: 99%